Postmodernism, Marxism and Versions of the Future: an Interview with Professor Martin Jay / Postmodernismo, marxismo y versiones del futuro: una entrevista con el profesor Martin Jay - Sanz Loroño, Miguel Angel (Historiografías, 2018)
A través de su interés en el postmodernismo y crítica de las metanarrativas, en esta entrevista el profesor Martín Jay aborda algunos de los principales temas que han centrado la atención de la teoría histórica recientemente. Temas como el giro hacia la experiencia histórica, la contribución de Hayden White a la comprensión de la narrativa y el lenguaje, o la importancia de Fredic Jameson, son traídos a colación en este texto. El profesor Jay también vuelve a algunos de sus temas iniciales y conocidos como la llamada French Theory, el filósofo alemán Theodor W. Adorno y la presencia del marxismo en los Estados Unidos.Palabras clavePostmodernismo, capitalismo tardío, marxismo, experiencia histórica. AbstractThrough his interest in postmodernism and in criticism to metanarratives, in this interview Professor Martin Jay tackles some of the main issues that have lately focused the attention of historical theory. Topics such as the turn towards historical experience, Hayden White’s contribution to understanding of narratives and language, or the importance of Fredric Jameson, are brought up in this text. Professor Jay also comes back to some of his former well-known themes such as the so-called French Theory, the German philosopher Theodor W. Adorno and the presence of Marxism in the United States.Key wordsPostmodernism, late capitalism, Marxism, historical experience.